Experimental Investigation on The Gasification of High-Ash Indian Coal and Biomass in a Bubbling Fluidized Bed using Air and Steam - Dave, Priyank; Parikh, Jigisha K.; Channiwala, Salim A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2026)
India produces significant amounts of biomass waste, including sugarcane bagasse and sawdust, as well as low-grade, high-ash coal – resources that are not fully tapped into despite their considerable energy potential. Gasification provides a clean and efficient technique for transforming these raw materials into valuable energy sources. This research outlines the design and development of a bubbling fluidized bed gasifier capable of handling high-ash coal (46% ash) and biomass, utilizing air and steam as gasifying agents. Experiments were performed to assess the effects of equivalence ratio (ER), temperature, and steam-to biomass (S/B) ratio on syngas composition. Raising the temperature from 500°C to 700°C significantly enhanced H2 and CO production across all feedstocks, indicating improved gasification efficiency at high temperatures. H2 concentrations increased from 6.7% to 9.1% for sawdust, 10.3–17.5% for bagasse, and 11.4–15.2% for high-ash coal. The optimal ER values for enhancing syngas quality were determined to be 0.35 for biomass and 0.43 for coal. Increasing the S/B ratio from 0.5 to 0.7 significantly increased H2 content, achieving 25.1% for sawdust and 23.3% for bagasse, attributed to the water-gas shift reaction. The energy balance analysis indicated energy outputs of 12.13 MJ/kg for sawdust, 16.79 MJ/kg for bagasse, and 17.72 MJ/kg for high-ash coal. These results validate the technical feasibility and operational versatility of the gasifier for various feedstocks. The research provides essential insights for optimizing gasification parameters, aiding in cleaner energy production and more efficient use of biomass and coal resources in India .